C-type related order in the defective fluorites La2Ce2O7 and Nd2Ce2O7 studied by neutron scattering and ab initio MD simulations. Issue 34 (15th August 2016) - Kalland, Liv-Elisif; Norberg, Stefan T.; Kyrklund, Jakob; Hull, Stephen; Eriksson, Sten G.; Norby, Truls; Mohn, Chris E.; Knee, Christopher S.
Abstract : We present a structural investigation of La2− x Nd x Ce2 O7 using molecular dynamics, in addition to X-ray powder diffraction and total scattering neutron powder diffraction, analysed using Rietveld refinement and the reverse Monte Carlo method. Abstract : This work presents a structural investigation of La2− x Nd x Ce2 O7 ( x = 0.0, 0.5, 1.0, 1.5, 2.0) using X-ray powder diffraction and total scattering neutron powder diffraction, analysed using Rietveld and the reverse Monte Carlo method (RMC). Ab initio molecular dynamics (MD) modelling is also performed for further investigations of the local order. The main intensities in the neutron diffraction data for the La2− x Nd x Ce2 O7 series correspond to the fluorite structure. However, additional C-type superlattice peaks are visible for x > 0 and increase in intensity with increasing x . The Nd-containing compositions ( x > 0) are best fitted with Rietveld analysis by using a combination of oxygen deficient fluorite and oxygen excess C-type structures. No indications of cation order are found in the RMC or Rietveld analysis, and the absence of cation order is supported by the MD modelling. We argue that the superlattice peaks originate from oxygen vacancy ordering and associated shift in the cation position away from the ideal fluorite site similar to that in the C-type structure, which is seen from the Rietveld refinements and the observed ordering in the MD modelling. The vacancies favour alignments in the 〈110〉, 〈111〉 and especially the 〈210〉 direction. Moreover, we find that such ordering might also be found to a small extent in La2 Ce2 O7, explaining the discernible modulated background between the fluorite peaks. The observed overlap of the main Bragg peaks between the fluorite and C-type phase supports the co-existence of vacancy ordered and more disordered domains. This is further supported by the observed similarity of the radial distribution functions as modelled with MD. The increase in long range oxygen vacancy order with increasing Nd-content in La2− x Nd x Ce2 O7 corresponds well with the lower oxide ion conductivity in Nd2 Ce2 O7 compared to La2 Ce2 O7 reported earlier.